A systematic in vitro study of the effect of normoglycaemic and hyperglycaemic conditions on the biochemical and cellular interactions of clinically-available wound dressings with different physicochemical properties - Shirin Saberianpour; Gianluca Melotto; Rachel Forss; Lucy Redhead; Susan Sandeman; Nadia Terrazzini; Dipak Sarker; Matteo Santin (PLoS ONE, 2025)
Diabetic foot, leg ulcers and decubitus ulcers affect millions of individuals worldwide leading to poor quality of life, pain and in several cases to limb amputations. Despite the global dimension of this clinical problem, limited progress has been made in developing more efficacious wound dressings, the design of which currently focusses on wound protection and control of its exudate volume. The present in vitro study systematically analysed seven types of clinically-available wound dressings made of different biomaterial composition and engineering. Their physicochemical properties were analysed by infrared spectroscopy, swelling and evaporation tests and variable pressure scanning electron microscopy. These properties were linked to the interactions with inflammatory cells in simulated normoglycaemic and hyperglycaemic conditions. It was observed that the swelling behaviour and evaporation prevention at different glucose levels depended more on the engineering of the fibres than on the hydrophilicity and hydrophobicity of their biomaterials. Likewise, the data show that the engineering of the dressings as either non-woven or woven or knitted fibres seems to determine the swelling behaviour and interactions with inflammatory cells more than their polymer composition. Dressings presenting absorbent layers made of synthetic, non-woven fibres supported the adhesion of monocytes macrophages and stimulate the release of factors known to play a role in the chronic inflammation. Non-woven absorbent layers based on carboxymethyl cellulose mainly stimulating the iNOS, an enzyme producing free radicals; in the case of Kerracel this was combined with a swelling of fibres preventing the penetration of cells. Kaltostat, an alginate-based wound dressing, showed the higher level of swelling and supporte the adhesion of inflammatory cells with limited activation. Knitted dressings showed a limited adhesion of inflammatory cells. In conclusion, this work offers insights about the interactions of these wound dressings with inflammatory cells upon exudate changes thus providing further criteria of choice to clinicians.